Modelado de un sistema de señalización, modificable dinámicamente, para un sistema de enrutamiento orientado a la gestión de emergencia. - Gastezzi Pacheco, Kendall Bruno (2015)
A Wireless Sensor Network is a set of sensor nodes, which are able to establish wireless communication among them, spatially allocated in order to monitor physical or environmental conditions. This paper is about the evaluation of the time it took to get over damages that may turned down some nodes in the network, in order to do this we simulate the most widely used AdHoc protocols with the help of NS3. When a case of an emergency occurs is vital and very decisive a fast evacuation of the environment where the emergency took place, therefore we choose the protocol that has a faster adaptability to events in the network, to accomplish this we test both protocols in several scenarios with different node densities and some percentage of damaged nodes.